Cost-effectiveness and epidemiological impact of gender-neutral HPV vaccination in Spain - Renata Linertová; Carmen Guirado-Fuentes; Javier Mar-Medina; Conor Teljeur (Taylor & Francis Group, 2022)
All EU countries have introduced Human papilloma virus (HPV) vaccination for adolescent girls and many countries are expanding the strategy to include adolescent boys. There is uncertainty about the cost-effectiveness and epidemiological impact of a gender-neutral HPV vaccination strategy. Here we present the results of an economic model adapted for Spain. Five vaccination strategies were compared from the Spanish healthcare system perspective, combining two vaccines (4-valent and 9-valent) in a gender-neutral or girls-only programme in a dynamic population-based model with a discrete-time Markov approach. Costs and benefits were discounted at 3%. The benefits of immunization were measured with quality-adjusted life years (QALYs), which are achieved by reducing the incidence of diseases attributable to HPV. Incremental cost-effectiveness ratio (ICER) was compared with the willingness-to-pay threshold in Spain. The two most effective strategies were compared: gender-neutral 9-valent vaccination vs. girls-only 9-valent vaccination, resulting in an ICER of € 34,040/QALY, and an important number of prevented cases of invasive cancers and anogenital warts. The sensitivity analysis revealed that gender-neutral 9-valent vaccination would become cost-effective if protection against oropharyngeal and penile cancers was included or if the price per dose decreased from €45 to €28. The gender-neutral 9-valent HPV vaccination in Spain offers more benefits than any other modeled strategy, although in the conservative base case it is not cost-effective. However, certain plausible assumptions would turn it into an efficient strategy, which should be borne in mind by the decision makers together with equity and justice arguments.